Ultrasound-Assisted Extraction (UAE) of Phytochemicals with Response Surface Methodology (RSM) in Curcuma Xanthorrhiza - Najiba zemi, Norazah Basar, Susilawati Toemen (International Journal of Advanced Science and Technology, 2020)
The genus Curcuma from the Zingiberaceae family consist of 80 species is widely recognized for its culinary and pharmaceutical application and has a significant effect on medicine, food, cosmetic industries, and economic. Considering an eco-friendly extraction method that provides the efficiency of the extraction, it is great of interest to explore the best optimum condition of parameters used in the extraction. This research is carried out to optimize the ultrasound-assisted extraction (UAE) of the extract from C. xanthorrhiza via Response Surface Methodology (RSM). Box-Behnken design (BBD) is used with three variables: extraction time (5-20 min), temperature (30-50°C) and liquid-solid ratio (6-10 mL/g). In the extracts, xanthorrhizol and curcumin are quantified using reversed-phase high-performance liquid chromatography combined with a diode array detector. The optimum condition of yield and concentration of xanthorrhizol are found at the extraction temperature of 50°C, time 20 minutes, and liquid-solid ratio8 mL/g. However, the optimum condition of curcumin is found at the extraction temperature 30°C, time 12.50 minutes, and 10 mL/g liquid-solid ratio. This research recommended that the ultrasound-assisted extraction method under specific parameters has favorable potential to be used in the extraction process which is useful for advanced research.